Accounting models challenged by environmental preoccupations: an analysis based on the OHADA accounting law. (2018) - Ndjetcheu, Louis
Recently there have been several articles focusing on environmental accounting in developed countries. On the contrary, findings which analyse this phenomenon in francophone Africa are rare, if not inexistent. The objective of this article is to re-examine the OHADA accounting model following the ratification of several laws and conventions by most of these countries and which regulate the propagation of environmental and social information by some African enterprises whose activities have negative consequences on the society. A qualitative analysis of the chart of accounts and OHADA financial statements based on a grill emulated from the study of Ernst and Ernst (1978) enables to suggest that the OHADA model does not conform to the different laws and conventions relative to environmental issues. This enables us to confirm that in OHADA countries the legal framework is in advance with respect to accounting law. This remark is a reflection of the bad governance of the OHADA institution in terms of adaption of the accounting model faced with the needs of the users and environmental transformations.